Tailored, theory-based strategies for engaging lowincome populations with a personal health record - Toscos, Tammy; D. Wright, Maria; Flanagan, Mindy E.; Kunjan, Kislaya; Olson-Miller, Amy; Doebbeling, Bradley N. (EAI Endorsed Transactions on Pervasive Health and Technology, 2017)
There remain significant barriers to the use of personal health records (PHRs), which limit potential benefits in underserved patient populations. Novel strategies must be developed to achieve the desired impact of PHRs on patient engagement and health outcomes. This paper describes the health information needs and technology preferences of adults seeking care in Community Health Centers (CHCs), which provide care to low-income, uninsured and underinsured patients. We offer design suggestions emerging from interviews with 43 CHC patients and 49 CHC staff members that explored many themes including: patient barriers to accessing health care, health information needs of patients between clinic visits, patient and clinic staff preferences for technology use, and PHR implementation approaches used in CHCs. Our findings provide a roadmap to greater engagement of patients via PHRs by expanding functionality, providing tailored patient messaging, and incorporating adult learning strategies.
Keywords: Pervasive health care; patient engagement; health information technology; communication technology; underserved populations; low income populations; personal health record